Filipendula vulgaris Moench Extracts: Phytochemical Research and Study of Their Cytotoxic and Antitumour Activity - Oksana Struk; Yurii Klymenko; Oleh Koshovyi; Andriy Grytsyk; Galyna Starchenko; Valdas Jakštas; Vaidotas Žvikas; Ain Raal (Applied Sciences)
Filipendula vulgaris Moench (syn. F. hexapetala Gilib., dropwort, Rosaceae) is widely used in folk medicine as an antitumour agent, but there is a lack of scientific knowledge about it. This research aimed to study the phytochemical composition and cytotoxic and antitumour activity of aqueous and aqueous–alcoholic extracts from rhizomes with roots of F. vulgaris to investigate their effect on the development of experimental Ehrlich ascites carcinoma in mice, and their effect on the animals’ lifespan. A total of 10 phenolics and 14 amino acids were determined by HPLC in the extracts. The dominant phenolic compounds were procyanidins B1, B2, and C1, as well as metabolites of the tannins (+)-catechin and epicatechin gallate. For the first time, 27 volatile substances were identified and semiquantified using GC-MS. The principal volatile components were palmitic acid (41.0%), methyl salicylate (24.2%), and benzyl salicylate (17.5%). The aqueous–alcoholic extract was significantly more effective than the aqueous one. The treatment of mice with Ehrlich carcinoma using the F. vulgaris aqueous–alcoholic extract normalised the studied indicators. The growth inhibition coefficient of Ehrlich ascites carcinoma was 62.3% and 65.8% on the 7th and 14th days, respectively. This was manifested in the inhibition of tumour growth based on a decrease in the content of ascites fluid in the abdominal cavity; a more intense manifestation of cytotoxic action on cancer cells; improvements in haematopoiesis, the antioxidant defence system, and the content of the studied bioelements in the blood serum; and an increase in the lifespan of experimental animals by around two times. The study results allow us to consider F. vulgaris rhizomes with roots as a promising anticancer agent for the design of pharmaceutical preparations and further study their effects on the human body.